Some reflections on the trial of violence against women with a gender perspective and criminal procedural designs: The case of jury in the province of Córdoba (Argentina) - Villanueva, Carlos Martín (2019)
Any discussion about gender violence, over the last decade in Argentina and especially in the province of Cordoba, has gained social visibility. In the first part, we will analyze, briefly, the most important legal reforms in Argentina about gender violence and in particular the incorporation of femicide. In the second part, we will focus on a legal proposal concerning juries that in the province of Cordoba have the jurisdiction to decide femicide. We conclude that it is possible to control a previously and posterior stereotype on gender in relation to the decision regarding its use.